METHOD FOR CRYSTALLIZATION OF IOPAMIDOL - PARK, JIN GYOU; LEE, IN GYU; CHOI, GYOUNG SUK; LEE, DONG YOUP; SONG, CHANG HYUN; LEE, DONG JOON (2000)
PURPOSE: Iopamidol having a pure anhydrous compound for X-ray contrast medium without a hydrate 1 and a hydrate 5 is provided by using a solvent having mixed water and alcohol. Thereby, it is possible to obtain iopamidol having a pure anhydrous compound with purity of at least 99.5% and yield of at least 90%, so that mass production is possible. CONSTITUTION: The method for crystallization of iopamidol contains following the steps of: solving an iopamidol in the vaporized water to vaporize the water; removing the vaporized water to add an alcohol; and then refluxing the mixture for 3-4hour to obtain the iopamidol of white crystal. A ratio of iopamidol to vaporized water is 10: 1(w/v) to 1: 1(w/v) and a ratio of iopamidol to alcohol is 1: 1(w/v) to 1: 10(w/v). The alcohol is consisted of ethanol and propanol. A ratio of iopamidol: water: ethanol is 4: 1: 8(w/v/v). When the reflux time is 4hour, anhydrous iopamidol having solubility of at least 80% is obtained. 본 발명은 X-ray 조영제중에서 범용적으로 많이 사용되는 이오파미돌(Iopamidol)의 신규한 결정화 방법에 관한 것이다. 이오파미돌의 결정은 무수화물, 1 수화물 및 5 수화물로 존재하며 결정화 방법에 따라 그 형태가 다르다. 본 발명은 순수한 무수물의 이오파미돌의 결정화에 있어서 기존의 방법과는 달리 이오파미돌 대비 증류수는 10:1 (w/v)∼1:1 (w/v)으로 하고 이오파미돌 대비 알콜은 1:1 (w/v)∼1:10 (w/v)로 하여 물과 알콜인 에탄올, 프로판올을 이오파미돌 대비 일정한 비율로 혼합하여 환류시켜 고순도 및 고수율로 이오파미돌을 결정화한다.